Neuromuscular control of the knee joint during basketball season in male youth players - Strnište, M.; Hulka, K.; Lehnert, M.; Maixnerová, E.; Vareková, R.; Lazecká, S. (Acta Gymnica, 2019)
Background: Basketball players are among the players with a great risk of anterior cruciate ligament injury due to the high-intensity manoeuvres which have been identified as very common factors preceding this injury.